2006
DOI: 10.1073/pnas.0602965103
|View full text |Cite
|
Sign up to set email alerts
|

Bases of biocontrol: Sequence predicts synthesis and mode of action of agrocin 84, the Trojan Horse antibiotic that controls crown gall

Abstract: Agrobacterium radiobacter K84, used worldwide to biocontrol crown gall disease caused by Agrobacterium tumefaciens, produces an antiagrobacterial compound called agrocin 84. We report the nucleotide sequence of pAgK84, a 44.42-kb plasmid coding for production of this disubstituted adenine nucleotide antibiotic. pAgK84 encodes 36 ORFs, 17 of which (agn) code for synthesis of or immunity to agrocin 84. Two genes, agnB2 and agnA, encode aminoacyl tRNA synthetase homologues. We have shown that the toxic moiety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 38 publications
0
74
0
2
Order By: Relevance
“…Database comparisons revealed that the backbone of pAMI2 described above is conserved in pAgK84 of Agrobacterium radiobacter K84, a plasmid responsible for the production of the antiagrobacterial compound agrocin 84 (21). Plasmids pAMI2 and pAgK84 carry related replication, partitioning, and transfer systems in synteny, which strongly suggests that they originate from a common ancestor replicon (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…Database comparisons revealed that the backbone of pAMI2 described above is conserved in pAgK84 of Agrobacterium radiobacter K84, a plasmid responsible for the production of the antiagrobacterial compound agrocin 84 (21). Plasmids pAMI2 and pAgK84 carry related replication, partitioning, and transfer systems in synteny, which strongly suggests that they originate from a common ancestor replicon (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…Many plant-associated bacteria make bacteriocins, such as agrocin, produced by Agrobacterium radiobacter strain K84. This bacteriocin excludes the crown gall pathogen A. tumefaciens from the infection court so effectively that A. radiobacter is widely used for biocontrol (54).…”
Section: Figmentioning
confidence: 99%
“…The first five structural genes, accABCDE, code for an ABC-type transport system that takes up agrocinopines as well as a unique antibiotic called agrocin 84 (27,34). Agrocin 84 is produced by A. radiobacter strain K84, which is antagonistic to A. tumefaciens strain C58 competing for agrocinopines that are produced by plants transformed by A. tumefaciens strain C58 (19,36,47,48,56,64,67). The last two genes, accF and accG, code for agrocinopine phosphodiesterase and arabinose phosphate phosphatase, respectively (34, 73).…”
mentioning
confidence: 99%